FROM UNIVERSITY TO WORKFORCE: CHALLENGES AND EXPERIENCES OF STUDENTS WITH DISABILITIES IN KAZAKHSTAN - Orynbassarov, Darkhan; Nuskabay, Assel; Seit, Ainur; Mamutov, Zhumabek (Farabi Journal of Social Sciences, 2025)
Purpose. This study explores the experiences of students with disabilities in Kazakhstan in relation to their academic processes and social inclusion within universities and workplaces. It aims to examine the challenges and opportunities these students face in academic participation, social life, and job placement. Design/methodology/approach. The research focuses on students and graduates with disabilities and is based on six in-depth interviews. A qualitative approach was adopted to capture their lived experiences and perspectives on inclusive education and transition to employment in Kazakhstan. Findings. The findings indicate that academic support is the most commonly provided service for students with disabilities, while social inclusion initiatives and career transition programs remain limited. Major challenges include restricted physical access to infrastructure, insufficient specialized assistance, and significant barriers to employment after graduation. Career preparation services were found to offer only superficial guidance, without providing clear direction for navigating diverse workplaces. Originality. This study contributes to the understanding of inclusive education in Kazakhstan by highlighting the gap between academic support and social or professional inclusion for students with disabilities. It provides new insights into how universities and employers can enhance accessibility, inclusivity, and post-graduation support systems. Key words: inclusive education: disability, University, students’ perceptions, social participation, challenges.